Perlindungan Hukum Pengguna Layanan Teknologi Finansial (Financial Technology) Pinjam Meminjam Uang Berbasis Teknologi Informasi (Peer To Peer Lending) - Nurasiah Harahap (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
Financial Technology is the implementation and utilization of technology to improve banking and financial services which are generally carried out by startup companies by utilizing the latest software, internet, communication and computing technologies.The research conducted was juridical empirical and normative juridical research, namely field research with interviews as a basis for problem solving and analyzing statutory regulations. The data used are primary and secondary data, then the data collection methods used in this study are library research and field research. The data analysis used is a qualitative method.The results show that the legal protection of users of the Financial Technology (Financial Technology) service of borrowing and borrowing money based on information technology (Peer to Peer Lending) has been carried out by the Financial Services Authority (OJK) and its staff by means of supervision, examination and investigation based on the Financial Services Authority Regulation No. 77 / POJK.01 / 2016 concerning Information Technology-Based Lending and Borrowing Services.The conclusion is that the legal protection of users of the Financial Technology (Financial Technology) service of lending and borrowing money based on information technology (Peer to Peer Lending) can be realized in a preventive and repressive manner. Basically, the Operator does not have direct legal consequences that make risk transfer to the Operator. Keywords: Financial Technology, Peer to Peer Lending, Legal Protection for Users / Consumers.